1997
DOI: 10.1056/nejm199707173370301
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Rheumatoid Arthritis with a Recombinant Human Tumor Necrosis Factor Receptor (p75)–Fc Fusion Protein

Abstract: In this three-month trial TNFR:Fc was safe, well tolerated, and associated with improvement in the inflammatory symptoms of rheumatoid arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
683
1
18

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,447 publications
(717 citation statements)
references
References 46 publications
15
683
1
18
Order By: Relevance
“…Thus, inflammatory actions on nerve endings, including nociceptive fibers, may result in long‐term sensitization, which contributes to chronic pain conditions. Proinflammatory cytokines like tumor necrosis factor (TNF) and interleukin 6 (IL‐6) are both of specific importance in RA pathogenesis, and specific cytokine blockade has been shown beneficial 22, 23. Both TNF and IL‐6 also affect pain thresholds in experimental arthritis 24, 25, as well as long‐term sensitization of joint nociceptors 26.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, inflammatory actions on nerve endings, including nociceptive fibers, may result in long‐term sensitization, which contributes to chronic pain conditions. Proinflammatory cytokines like tumor necrosis factor (TNF) and interleukin 6 (IL‐6) are both of specific importance in RA pathogenesis, and specific cytokine blockade has been shown beneficial 22, 23. Both TNF and IL‐6 also affect pain thresholds in experimental arthritis 24, 25, as well as long‐term sensitization of joint nociceptors 26.…”
Section: Discussionmentioning
confidence: 99%
“…37 Randomized, double-blind, placebo-controlled trials showed that human p75 sTNFR:Fc fusion protein treatment yielded significant clinical benefits, with minimal toxicity, in patients with RA who had inadequate responses to other disease-modifying drugs. 17 Soluble cytokine receptors may have a distinct advantage over other TNF-neutralizing agents, such as monoclonal antibodies, in terms of immunogenicity. Indeed, no antibodies against sTNFR:Fc were detected in clinical studies involving patients with RA and normal volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, no antibodies against sTNFR:Fc were detected in clinical studies involving patients with RA and normal volunteers. 17,38 However, due to the chronic characteristics of autoimmune arthritis, subcutaneous injection of 25 mg sTNFR:Fc twice weekly is required to obtain a significant clinical benefit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the aim of medical treatment of RA patients has shifted from the short-term improvement of the quality of life (QOL) through pain relief to the long-term improvement of QOL by the prevention of joint damage and improved mortality. Tumor necrosis factor (TNF) is considered to be a major cytokine involved in RA pathogenesis, and anti-TNF therapy using monoclonal antibodies or fusion proteins was the first anti-cytokine therapy to be developed for RA [46]. Anti-TNF therapy has achieved great success in suppressing rheumatoid inflammation and preventing the progression of joint damage in RA patients [79], thereby confirming that TNF indeed appears to be critically involved in the pathogenesis of RA synovitis.…”
Section: Introductionmentioning
confidence: 99%